Home Automation Security System - TANG, LOK YUAN (Progress in Engineering Application and Technology, 2023)
At this era, the pandemic still has impacted on economic uncertainty among the people’s lives and livelihoods. Thus, this situation has caused the cases of burglary have been increased within these few years. By this time a remotecontrol system that will be easily controlled by the house owner is able to penetrate the market. This report presents the basic design of a Home Automation Security System. This is a proposal about how to build a low-cost security system to protect both the life and property of the house owner. After this project, I have understood how important it is that home security systems will reduces of chance of intrusion. Hence, using the micro controller technology I design a Home Automation System where the entire electrical item will be controlled. With the Wi-Fi module people can also set door locks with the appropriate use of motion sensors while the alarm of buzzer rings to give notification to surrounding around the house and makes an automatic SMS notification system by Blynk application. Compared to others this system is low cost, attractive user-friendly interface which is platform independent and it’s very easy to install. After implementation of all functions, the system is tested by entering coding into the Arduino IDE and it works successfully.